2011
DOI: 10.1073/pnas.1100869108
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channels contribute to colonic hypersensitivity in a rat model of irritable bowel syndrome

Abstract: The symptoms of irritable bowel syndrome (IBS) include significant abdominal pain and bloating. Current treatments are empirical and often poorly efficacious, and there is a need for the development of new and efficient analgesics aimed at IBS patients. T-type calcium channels have previously been validated as a potential target to treat certain neuropathic pain pathologies. Here we report that T-type calcium channels encoded by the Ca V 3.2 isoform are expressed in colonic nociceptive primary afferent neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 46 publications
8
98
0
Order By: Relevance
“…These findings are in agreement with the recent evidence that Ca v 3.2, among the three isoforms of T-type Ca 2+ channels, in the sensory neurons plays a major role in processing of somatic (11) and visceral pain (12). Previously, we have shown that luminal H 2 S-induced colonic pain / referred hyperalgesia is prevented by pretreatment with zinc chloride (ZnCl 2 ) and that luminal zinc chelators mimic the T-type Ca 2+ channel-dependent colonic pain / referred hyperalgesia caused by H 2 S (13).…”
supporting
confidence: 82%
“…These findings are in agreement with the recent evidence that Ca v 3.2, among the three isoforms of T-type Ca 2+ channels, in the sensory neurons plays a major role in processing of somatic (11) and visceral pain (12). Previously, we have shown that luminal H 2 S-induced colonic pain / referred hyperalgesia is prevented by pretreatment with zinc chloride (ZnCl 2 ) and that luminal zinc chelators mimic the T-type Ca 2+ channel-dependent colonic pain / referred hyperalgesia caused by H 2 S (13).…”
supporting
confidence: 82%
“…Stimulation of T-type calcium channels, subtype Ca v 3.2 on the primary signaling visceral afferents was associated with symptoms similar to the irritable bowel syndrome in the animal model. Behavioral symptoms resolved after the application of T-type calcium channels inhibitor [44]. Afferent transduction from mesentery in the experimental intestinal ischaemia was blocked by nifedipine, an L-type calcium channels inhibitor [45].…”
Section: Other Types Of Calcium Channel Blockers Used In the Treatmenmentioning
confidence: 95%
“…Therefore, enhancement of Ca V 3.2 channel expression/activity contributes to pain hypersensitivity. Although no mutations in Ca V 3.2 that result in increased pain in humans have been reported in the literature, peripheral nerve injury or inflammation (Jagodic et al, 2008;García-Caballero et al, 2014), diabetes (Jagodic et al, 2007;Messinger et al, 2009), and colonic inflammation (Marger et al, 2011a) all give rise to increased DRG neuron T-type calcium currents in rodents. At least two mechanisms appear to contribute to this phenomenon: an enhancement of Ca V 3.2 channel trafficking, due to glycosylation in the case of diabetic pain (Orestes et al, 2013;Weiss et al, 2013), and stabilization of these channels as a result of enhanced deubiquitination (García-Caballero et al, 2014).…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%